Report on the SCRA Nuts and Bolts Workshop II: case studies of citrus greening, Ultra-low Gossypol Cotton, and blight tolerant, low-acrylamide potato - Hood, Elizabeth E. (GM Crops Food, 2019)
To be commercialized and grown in the US, genetically engineered (GE) crops typically go through an extensive food, feed, and environmental safety assessment process which, in certain instances, requires complex consultations with three different US regulatory agencies. Many small market, niche, and specialty crops have been genetically engineered using the modern tools of recombinant DNA but few have been commercialized due to real or perceived regulatory constraints. This workshop discussed the practical aspects of developing dossiers on GE specialty, niche, or small-market crops/products for submission to US regulatory agencies. This workshop focused on actual case studies, and provided an opportunity for public or private sector scientists and crop developers to spend time with regulatory officials to learn the specifics of compiling a dossier for regulatory approval. The objective of the workshop was to explain and demystify data requirements and regulatory dossier compilation by small companies, academics, and other developers.